The Effects of Telenursing on Stress in Mothers with Premature Infants - Elham Asghari; Azam Shirinabadi Farahani; Manigheh Nourian; Hossein Bonakchi; Sara Gholami (Mashhad University of Medical Sciences, 2021)
Background: The birth and protection of premature infants cause major stress in their mothers. The implementation of strategies to reduce this stress is one of the major tasks of nursing researchers. Aim: This study aimed to investigate the effects of telenursing on the ‎level of stress in mothers with premature infants, following the infants' discharge from ‎the Neonatal Intensive Care Unit. Method: This clinical trial was conducted on 120 mothers who were randomly assigned into intervention and control groups. Data collection was performed using Barry and Jones's parental stress scale and the maternal and neonatal demographic questionnaire. Telenursing was performed to educate mothers in the intervention group using the Telegram application for four weeks. The control group only received the usual care at discharge. Data were collected one day after discharge, one day, and four weeks after intervention and analyzed in SPSS software (version 19) through the Kolmogorov-Smirnov test, independent t-test, and Kruskal-Wallis test. Results: The mean maternal stress level±SD was estimated at 70.8±8.8 and 70.6±8.9 in the intervention and control groups, respectively. These numbers changed to 53.0±1.8 and 59.8±2.8 in the intervention group and 68.1±2.4 and 59.8±5.1 in the control group immediately and four weeks after intervention (telenursing), respectively. Therefore, the mothers in the intervention group experienced less stress (P<0.001). Implications for Practice: The application of this low-cost and affordable method is recommended for its impact on the reduction of mean maternal stress levels in the intervention group compared to the controls.